The truth as told by Mason Buttle - Connor, Leslie (Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2018)
As he grieves his best friend Benny's death, Mason and his friend Calvin, who are targeted by the neighborhood bullies, create an underground haven for themselves, but when Calvin goes missing Mason finds himself in trouble.